Effect of Atractylodes macrocephala on Hypertonic Stress-Induced Water Channel Protein Expression in Renal Collecting Duct Cells. (14th November 2012) - Lee, Yong Pyo; Lee, Yun Jung; Lee, So Min; Yoon, Jung Joo; Kim, Hye Yoom; Kang, Dae Gill; Lee, Ho Sub
Abstract : Edema is a symptom that results from the abnormal accumulation of fluid in the body. The cause of edema is related to the level of aquaporin (AQP)2 protein expression, which regulates the reabsorption of water in the kidney. Edema is caused by overexpression of the AQP2 protein when the concentration of Na + in the blood increases. The rhizome of Atractylodes macrocephala has been used in traditional oriental medicine as a diuretic drug; however, the mechanism responsible for the diuretic effect of the aqueous extract from A. macrocephala rhizomes (AAMs) has not yet been identified. We examined the effect of the AAM on the regulation of water channels in the mouse inner medullary collecting duct (mIMCD)-3 cells under hypertonic stress. Pretreatment of AAM attenuates a hypertonicity-induced increase in AQP2 expression as well as the trafficking of AQP2 to the apical plasma membrane. Tonicity-responsive enhancer binding protein (TonEBP) is a transcription factor known to play a central role in cellular homeostasis by regulating the expression of some proteins, including AQP2. Western immunoblot analysis demonstrated that the protein and mRNA expression levels of TonEBP also decrease after AAM treatment. These results suggest that the AAM has a diuretic effect by suppressing water reabsorption via the downregulation of the TonEBP-AQP2 signaling pathway.